Rancang Bangun Aplikasi Chatting Berbasis Web Menggunakan Docker - Adinta, Firlya; Neforawati, Indri (P3M Politeknik Negeri Banjarmasin, 2017)
The development of information technology is accompanied by development of support tools that allow users of technology to help the daily work and can communicate with each other. Web-based chat application is one alternative that can be used if the user does not want to perform the installation of chat applications on their phone or desktop. In making the chat application using virtual machine technology that is used to run an application. Mechanical containerize (container-based virtualization) is present as a solution of an increase in the number of hosted web application that must be followed by an increase in the quality and quantity of resources. Docker is a software which adopted the technique containerize and increasingly applied in the application development environment. This study tried to design using a web-based chat aplikasai Docker technology in the manufacture of a chat application